#MídiaNinjaAoVivo estratégias de produção de sentido e afeto em contra-narrativas de manifestações sociais - Santos, Diogo Costa dos (2019)
The dissertation identifies the strategies employed by the media activist movement Mídia Ninja to produce the sense of police repression and the feeling of indignation (cognitive-sentimental effects) in “live” counter-narratives of social manifestations. It starts from the assumption that such effects are produced from what Ninja Media reveals and as it reveals during the vigilance exercised by members of the Shock Police movement (representation of the state force) in street protests. It analyzes the content and poetics of 32 lives of 19 Brazilian social manifestations transmitted by the movement page on Facabook between April 2016 and September 2018. It aims to identify the strategies employed by the media activist movement Ninja Media in the production of cognitive-sentimental effects on “live” storytelling. It employs as analytical operators the content analysis method to identify what Ninja Media reveals from police surveillance, and adapted categories of the film's poetic analysis method to identify how it reveals. Presents the strategies of disclosure of police violence actions, and evidence of police violence as a result of content analysis, and narrative tactics (contextualization of violence, characterization of evidence, testimonies, updating and constitutionalization); performative (self-protection and conflict) and positioning (camera approaches and distances) as poetic forms of revelation of actions and evidence for the production of effects. It observes the strategies of revelation of actions and signs of police violence, respectively, in real time and in dead time, two "live" temporal regimes in the counter narratives. Of the final considerations, it emphasizes that the cognitive-sentimental counter-narratives produced by the social movement the Mídia Ninja movement frames police violence in the context of manifestations to produce the meaning effect of institutionalized state violence, and that the subjectification of the point of view visually embodies the counter-narrative, and configures a way of producing the affective effect of feeling.